Stress Resistance Screen in a Human Primary Cell Line Identifies Small Molecules That Affect Aging Pathways and Extend Caenorhabditis elegans' Lifespan. Issue 2 (1st February 2020) - Zhang, Peichuan; Zhai, Yuying; Cregg, James; Ang, Kenny Kean-Hooi; Arkin, Michelle; Kenyon, Cynthia
Abstract: Increased resistance to environmental stress at the cellular level is correlated with the longevity of long-lived mutants and wild-animal species. Moreover, in experimental organisms, screens for increased stress resistance have yielded mutants that are long-lived. To find entry points for small molecules that might extend healthy longevity in humans, we screened ∼100, 000 small molecules in a human primary-fibroblast cell line and identified a set that increased oxidative-stress resistance. Some of the hits fell into structurally related chemical groups, suggesting that they may act on common targets. Two small molecules increased C. elegans ' stress resistance, and at least 9 extended their lifespan by ∼10–50%. We further evaluated a chalcone that produced relatively large effects on lifespan and were able to implicate the activity of two, stress-response regulators, NRF2 / skn-1 and SESN / sesn-1, in its mechanism of action. Our findings suggest that screening for increased stress resistance in human cells can enrich for compounds with promising pro-longevity effects. Further characterization of these compounds may reveal new ways to extend healthy human lifespan.